Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1562/2005-07-07-ra-603
|View full text |Cite
|
Sign up to set email alerts
|

Water/Silica Nanoparticle Interfacial Kinetics of Sulfate, Hydrogen Phosphate, and Dithiocyanate Radicals

Abstract: The values of the rate constants for the reactions of the sulfate (2.5 x 10(9) M(-1) s(-1)) and hydrogen phosphate (2.2 x 10(8) M(-1) s(-1)) radicals with silica nanoparticles are obtained by flash photolysis experiments with silica suspensions containing S(2)O(8)(2-) or P(2)O(8)(4-), respectively. The interaction of these radicals with the silica nanoparticles leads to formation of transients, probably adsorbed sulfate and hydrogen phosphate radicals, with absorption maxima at around 320 and 350 nm, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 52 publications
2
18
0
Order By: Relevance
“…The previous results clearly indicate that Cl • and Cl 2 •− radicals interact with the NP surface. Moreover, in aqueous suspensions of pH < 5, silica NS have almost all its surface silanols undissociated (pK ag ≈4.5 and pK as ≈8.5 for the deprotonation of geminal and single silanols, respectively [19,20]). The lack of reaction between the Cl • /Cl 2 •− radicals and the NP surface at pH < 5, and the higher rates observed with increasing pH, clearly indicate that the deprotonated silanols are the reactive surface species, as shown in .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The previous results clearly indicate that Cl • and Cl 2 •− radicals interact with the NP surface. Moreover, in aqueous suspensions of pH < 5, silica NS have almost all its surface silanols undissociated (pK ag ≈4.5 and pK as ≈8.5 for the deprotonation of geminal and single silanols, respectively [19,20]). The lack of reaction between the Cl • /Cl 2 •− radicals and the NP surface at pH < 5, and the higher rates observed with increasing pH, clearly indicate that the deprotonated silanols are the reactive surface species, as shown in .…”
Section: Resultsmentioning
confidence: 99%
“…The absorbance of SiO • surface radicals strongly depends on the pH of the suspensions and despite that a broader absorption band was observed for suspensions of higher pH, it was not possible to differentiate the absorption of SiO • radicals formed from geminal or single silanols (19,20). Therefore, average absorption coefficients for SiO • radicals were estimated for each pH of the suspensions relative to the reported average value at 600 nm and pH 8.3, < ε 600 > pH 8 = 2100 M −1 cm −1 (20). The average absorption coefficients at the different wavelengths λ and suspension pH, < ε λ > pH , were calculated according to Eq.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if the spectra agree in general well, slight differences can be seen which could be of importance for spectroscopic studies. With the exception of Adams et al [74] and Caregnato et al [75] the maximum absorption is found around l % 478 nm. In the study of Caregnato and coworkers [75] the whole absorption band is blue-shifted by approximately 15 nm.…”
Section: Spectramentioning
confidence: 89%
“…With the exception of Adams et al [74] and Caregnato et al [75] the maximum absorption is found around l % 478 nm. In the study of Caregnato and coworkers [75] the whole absorption band is blue-shifted by approximately 15 nm. The spectra published by Czapski et al [76] shows a higher absorption at the peak absorbance.…”
Section: Spectramentioning
confidence: 89%